DNA Replication Controls - Eishi Noguchi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The conditions for DNA replication are not ideal, owing to endogenous and exogenous replication stresses that lead to arrest of the replication fork. Arrested forks are among the most serious threats to genomic integrity because they can break or rearrange, leading to genomic instability, which is a hallmark of cancers and aging-related disorders.